Packing for Mars for kids - Roach, Mary (Norton Young Readers, 2022)
Provides answers to kids' questions about space travel and life without gravity, and explores how everything from food to living in close quarters with other people to going to the bathroom has been engineered by NASA for astronauts living in space. Features interviews with astronauts and NASA engineers. Includes black-and-white photographs.